The nature and extent of mother tongue interference by Sepedi on the effectiveness of learning English among Information Technology foundation students at Tshwane University of Technology - Thembekwayo, Sophie Suzan (University of Pretoria, 2015)
Mini-dissertation (MA)--University of Pretoria, 2014.